Análise ecotoxicológica do efluente da indústria de beneficiamento da castanha de caju antes e após tratamento em reator aeróbio inoculado com fungos - Pimentel, Marcionília Fernandes (2008)
The cashew nut improvement is a very important and well-developed activity in almost all states of northeast Brazil, especially Ceará. However, there are few studies regarding the contribution of the cashew nut industry to environmental pollution in Ceará. This industry’s wastewater contains traces of cashew nut shell liquid (CNSL), in which phenols and other toxic aromatic compounds are present. The aim of this research was to assess the effectiveness of the treatment made by the industry (RAW and TREATED effluents) and the viability of a fixed bed bioreactor inoculated with the fungi Aspergillus niger in the treatment of the cashew nut industry’s wastewater samples using Artemia sp. acute toxicity test. In addition, levels of total phenols and chemical oxygen demand (COD) were determined. Wastewater samples were collected weekly from September 2007 until March 2008 in an industry located at Fortaleza city. The results of the acute toxicity tests were compared using the LC50 values and the dead nauplii number among 30 exposed at the 4% concentration. The results showed that both wastewater are highly toxic on 4% concentration with the mortality of almost all the organisms (RAW = 29.6 ± 0.4 e TREATED = 29.2 ± 0.1), demonstrating the ineffectiveness of the treatment made by the industry on the toxicity removal. The same occurred with total phenols and COD analyses. Regarding the biological treatment conducted in the laboratory, it is possible to note a great performance on toxicity, phenols and COD removal. The mean of dead nauplii for INFFLUENT after 24 hours was equal to 21.1 ± 2.8 nauplii, while after 48 hours was 25.4 ± 2.1. For EFFLUENT the mean of dead organisms after 24 hours was equal to 1.3 ± 0.8, while after 48 hours was 4.9 ± 1.9. The mean values obtained from total phenols analysis were 1.16 ± 0.27 mg/L (INFFLUENT) and 0.22 ± 0.06 mg/L (EFFLUENT) (p < 0.05). The highest value for phenol removal of the effluent was 98.1%. The mean value of COD was 1328.0 ± 123.4 mg de O2/L for INFFLUENT effluent and 231.2 ± 41.9 mg de O2/L for EFFLUENT (p < 0.05). The bioreactor reached levels of COD removal about 95.8%. A strong positive correlation was observed between toxicity and total phenols concentration and between toxicity and COD. A microbiological analysis of the final effluent were carried out, showing the presence of yeast instead of filamentous fungi. In conclusion the fixed bed fungal bioreactor can be considered an alternative for the biological treatment on this kind of wastewater.